Ruling Second-hand Clothes Trade: An Analysis of International Environmental Law - Amalia Zuhra; Arlina Permanasari; Gisca Nurannisa; Idris, Siti Hafsyah; Nasywaan, Muhammad Falih (University of Jember, 2025)
The second-hand clothing trade has emerged as a significant global industry, with the export and import of used clothing playing a vital role in the worldwide economy. However, the environmental impact of this trade has become a significant concern, particularly in developing countries that receive large quantities of used clothing. Reusing used clothing can be motivated by various considerations, such as charity, economic issues, reducing emissions and water use, and as benefits for prisoners during wartime. However, it is still unclear how much it can improve the sustainability of the apparel sector. According to the U.S. Environmental Protection Agency's most recent estimates, Americans dumped more than 21 billion pounds of clothing and other textiles into landfills in 2015. This amount is a significant increase from 12.5 billion pounds in 2000 and 4.6 billion pounds in 1980. Yet the proliferation of the inexpensive, disposable clothing known as